(untitled) (Research, Society and Development, 2021)
Objective: To identify interventions applied to the prescription, use and administration of medications as a strategic factor for patient safety. Method: Systematic review. Results: Twenty studies carried out on five continents, encompassing low-, middle- and high-income countries, were retrieved. As for the study designs used, there is 1 randomized controlled clinical study, 2 cohort studies, 10 cross-sectional studies, 1 economic study, 5 systematic reviews and 1 experience report. The categories of interventions regarding structural and technological, organizational, and professional, regulatory, educational, financial impact and interdisciplinary and multifaceted aspects are presented. Conclusion: The existence of different interventions that promote safe drug use practices in the hospital environment is recognized.